Shortages and Improvements of Medical Chatbots and Virtual Assistants in Medicine (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article explores the shortages and improvements of medical chatbots and virtual assistants in the field of medicine. The shortages of medical chatbots and virtual assistants are discussed in detail. The article highlights the lack of contextual understanding, ethical concerns and liability, and limited emotional intelligence as significant challenges. It explains how these limitations can result in inaccurate or incomplete responses, raise concerns regarding accountability and patient privacy, and lead to a lack of empathy in patient interactions. The article further elaborates on additional improvements, including the integration of cultural sensitivity, handling of complex cases, multimodal communication, continuous learning, integration with IoT devices, and enhanced privacy and data security. These improvements aim to address the limitations and enhance the capabilities of medical chatbots and virtual assistants.